Examination of failed retrieved temporomandibular joint (TMJ) implants. (1st March 2016) - Kerwell, S.; Alfaro, M.; Pourzal, R.; Lundberg, H.J.; Liao, Y.; Sukotjo, C.; Mercuri, L.G.; Mathew, M.T.
Graphical abstract: Abstract: In the management of end-stage temporomandibular joint disorders (TMD), surgeons must often resort to alloplastic temporomandibular joint (TMJ) total joint replacement (TJR) to increase mandibular function and form, as well as reduce pain. Understanding wear and failure mechanisms of TMJ TJR implants is important to their in vivo longevity. However, compared to orthopedic TJR devices, functional wear of failed TMJ TJR implants has not been examined. Not only do wear and corrosion influence TJR implant in vivo longevity, but so does reactivity of peri-implant tissue to these two events. The aim of this study was to examine and report on the wear of retrieved, failed metal-on-metal (MoM), metal-on-polymer (MoP), and titanium-nitride coated (TiN Coated) TMJ TJR implant components. A total cohort of 31 TMJ TJR devices were studied of which 28 were failed, retrieved TMJ TJRs, 3 were never implanted devices that served as controls. The mean time from implantation to removal was 7.24 years (range 3–15), SD 3.01. Optical microscopy, White Light Interferometry (WLI), Scanning Electron Microscopy (SEM), and Raman spectroscopy were utilized to characterize the surfaces of the devices. Data was acquired and evaluated by analyzing alloy microstructure. Substantial surface damage was observed between the articulating areas of the condylar head and the glenoid fossa components. Damage included pitting corrosion, evidence of deposited corrosion products, specific wear patterns, hard phases, surface depressions, and bi-directional scratches. Electrochemical analysis was performed on the MoM Control, retrieved, failed MoM, and TiN Coated devices. Electrochemical tests consisted of open circuit potential (OCP) and electrochemical impedance spectroscopy (EIS) tests conducted using the condylar head of the retrieved failed devices. EIS confirmed material properties as well as corrosion kinetics in vivo help to mitigate corrosion as reflected by the Raman spectroscopy results. In summary, this study demonstrated the role of wear and corrosion interactions on the early failure of TMJ TJR devices. Since the materials employed in most orthopedic TJR devices are similar to those used in TMJ TJR implants, studies such as this can provide data that will improve future embodiment paradigms for both. Further studies will include in vitro investigation of corrosion kinetics and the underlying tribocorrosion mechanism of TMJ TJR devices. Statement of Significance: An attempt is made in this study, to examine the retrieved TMJ implants and conduct surface and electrochemical analysis; further a translation research approach is employed to compare the observations from the total hip replacement (THR) retrievals. A total cohort of 31 TMJ TJR devices were studied of which 28 were failed, retrieved TMJ TJRs, 3 were never implanted devices that served as controls. Data was acquired and evaluated by analyzing alloy microstructure. Substantial surface damage was observed between the articulating areas of the condylar head and the glenoid fossa components. Electrochemical analysis was performed on the MoM Control, retrieved, failed MoM, and TiN Coated devices. This study demonstrated the role of wear and corrosion interactions on the early failure of TMJ TJR devices. Since the materials employed in most orthopedic TJR devices are similar to those used in TMJ TJR implants, a comparison study was conducted.